The Politeness Strategies of Criticism in Gorontalo Community: A Socio-pragmatic Study - Fajrul Shidiq Djunu (Hasanuddin University, 2025)
Criticism is a speech act that tends to damage social relationships between individuals. Therefore, criticism needs to be constructed in such a way using politeness strategies so that the level of threat that can damage interpersonal relationships can be reduced. This socio-pragmatic study aims to find out how politeness strategies are applied in speech acts of criticism used by the Gorontalo community in different situations. The Gorontalo people are one of the tribal groups in Indonesia located on the island of Sulawesi, which has language and cultural differences with other Indonesian tribes. This study uses the Discourse Completion Task (DCT) as the data collection technique, which is an elicitation method in the form of a questionnaire equipped with situational descriptions to facilitate completion. The questionnaire, containing nine different situations designed to trigger criticism. The DCT was distributed to 45 Gorontalo people who have different backgrounds. The results of the data analysis in this study show that in conveying criticism, the Gorontalo community employed the forms of politeness strategies include bald-on record, positive politeness, negative politeness, and off-record. Furthermore, this community tends to use politeness strategies that are influenced by two factors: the situational context and the social context. The situational context refers to the specific situation that triggers criticism. Meanwhile, the social context refers to the difference in social class between speakers and interlocutors, where the older/higher the position, the more polite the language used.